Genetic profile and mutation spectrum of Leber congenital amaurosis in a larger Indian cohort using high throughput targeted re‐sequencing. Issue 2 (25th January 2018) - Srikrupa, N.N.; Srilekha, S.; Sen, P.; Arokiasamy, T.; Meenakshi, S.; Bhende, M.; Kapur, S.; Soumittra, N.
Abstract : Frequency of mutations in 14/20 Leber congenital amaurosis (LCA) candidate genes in the 61% (56/92) Indians with GUCY2D gene contributing the highest (13%). Abstract : To provide a comprehensive data on the prevalence of mutations in Leber congenital amaurosis (LCA) candidate genes from a larger Indian cohort. Ninety‐two unrelated subjects were recruited after complete ophthalmic examination and informed consent. Targeted re‐sequencing of 20 candidate genes was performed using Agilent HaloPlex target enrichment assay and sequenced on Illumina MiSeq platform. The data were analyzed using standard bioinformatics pipeline, variants annotated, validated and segregated. Genotype‐phenotype correlation was performed for the mutation‐positive cases. Targeted next generation sequencing (NGS) for the 20 candidate genes generated data with an average sequence coverage and depth of 99.03% and 134X, respectively. Mutations were identified in 61% (56/92) of the cases, which were validated, segregated in the families and absent in 200 control chromosomes. These mutations were observed in 14/20 candidate genes and 39% (21/53) were novel. Distinct phenotypes were observed with respect to genotypes. To our knowledge, this study presents the first comprehensive mutation spectrum of LCA in a large Indian cohort. The mutation‐negative cases indicate scope for finding novel candidate gene(s) although mutations in deep intronic and regulatory regions cannot be ruled out.